MENINGKATKAN KETERAMPILAN BERMAIN BOLA BASKET MELALUI MEDIA AUDIO VISUAL - Rohani, Rohani (Jurnal Master Penjas & Olahraga, 2021)
The purpose of this study is to improve learning outcomes in basketball games; passing, dribbling, and shooting through audiovisual media in class IX.A SMP Negeri 1 South Tambun. The research subjects were 37 students of IX.A from SMP Negeri 1 South Tambun. The research method used is the Kemmis model school action research which consists of two cycles. Data collection techniques in the research were obtained from tests, observations, interviews, and documentation. The results obtained by the test result data evaluation of learning that has increased each cycle, the test results obtained a pre-cycle average value of 74,10 with mastery learning 37,84%, which has increased in the cycle I average value of 79,28 with mastery learning 70,27%, which has increased in the cycle II average value of 81,76 with mastery learning 81,08%. The conclusion of this study is through audio-visual media can improve learning outcomes in basketball games; passing, dribbling, and shooting in class IX.A SMP Negeri 1 South Tambun.